Long-term persistence of steppe vegetation in the highlands of Arasbaran protected area, northwestern Iran, as inferred from a pollen record. (2nd January 2021) - Ramezani, Elias; Talebi, Taravat; Alizadeh, Kamaledin; Shirvany, Anoushirvan; Hamzeh'ee, Behnam; Behling, Hermann
Abstract: Palynological analysis and radiocarbon dating of a short sediment core from a high-altitude mire in the Arasbaran area of northwestern Iran reveals long-term vegetation dynamics, climate change and anthropogenic impact. Our findings indicate the prevalence of semi-desert steppe vegetation, with a variety of Asteraceae – mainly Lactuceae – species from 3000 to 1440 cal yr BP. This period is followed by a higher occurrence of Artemisia spp. and Brassicaceae (1440–1330 cal yr BP), a re-expansion of Lactuceae (1330–1030 cal yr BP) and Brassicaceae (1030–330 cal yr BP) and, finally, Caryophyllaceae species (since 330 cal yr BP). The reconstructed millennia-long dry climate in the highlands of northwestern Iran is in good accordance with climate reconstructions from other east Mediterranean sites. Two phases of moister conditions between 2100–1400 and 1000–350 cal yr BP would correspond to altitudinal Quercus – Carpinus forest expansion in the Arasbaran area. The earliest indication of anthropogenic activity in the area dates back to the onset of the record, around 3000 cal yr BP. The occurrence of small maxima of Juglans regia, Corylus avellana and Cornus mas pollen at around 1350 cal yr BP is interpreted to reflect a temporary expansion of fruit cultivation. For the last millennium the occurrence of pollen attributable to Polygonum, Euphorbia, Plantago and Rumex suggests a diversification of steppe vegetation, which may reflect intensified agropastoral activities in the Arasbaran highlands. Based on our pollen record, the regional vegetation in the Kalan area remained largely stable over the last three millennia. However, changes in local hydrology caused substantial changes in wetland vegetation.